Kewenangan Pengadilan Niaga dalam Penyelesaian Sengketa Bisnis - Agus Iskandar (PRANATA HUKUM, 2012)
The title of this research is the study of the Authority of the Commercial Court in Business Disputes Settlement. The main issues of this research are as follows: (1) What is the authority of the Commercial Court in the settlement of business disputes, due to unclear object of commercial case which can be handled by the Commercial Court? The results of this research are as follows: First, the authority of theÂ Commercial Court under the bankruptcy law is to examine and adjudicate bankruptcy and other commercial cases.Â In addition to bankruptcy cases, the cases which are currently examined cover intellectual Property Right cases such as Industrial Design, Integrated Circuits Layout Design, Patent, brand and Copyright cases, whereas business disputes filed to the Commercial Court not provided under the Law are cases related to banking, trade agreements, consumer protection, insurance, corporation, transportation and capital markets.